UJI KEMAMPUAN Bacillus sp. ASAL PERSAWAHAN KALIMANTAN SELATAN DALAM MEMACU PERTUMBUHAN TANAMAN PADI (Oryza sativa L.) - Asniah Asniah; Noor Aidawati; Fakhrur Razie (Agroekotek View, 2019)
PGPR is a group of active bacteria colonized plant roots and well developed that is rich in organic material. This research was conducted in the laboratory of plant pathology greenhouse in the Faculty of Agriculture University of gastric Mangkurat Banjarbaru, which funded in May–August 2018. From the experiment there are five treatment four times and repeats. The treatment is A: Bacillus isolate: Marabahan, B: Bacillus isolate Kandangan, C: Bacillus isolate, Barabai, D: isolate Bacillus-Banjarbaru pelaihari, E: control (no Bacillus). Results of the study showed rice was given the inoculation with Bacillus spp. shows the number of saplings, plant height, wet weight of the plantlets, productive plants and plant dry weight was higher if compared with rice not applicable isolate Bacillus spp. isolates showed these Bacillus spp. were able to spur the growth of the rice plant.